Lack of neutrality among village officials in conflict resolution and law enforcement in Lebong Regency - Mike Jayanti; Heni Nopianti; Ika Pasca Himawati (Universitas Muhammadiyah Malang, 2025)
Law Number 6 of 2014 concerning Villages provides a legal basis for village officials in exercise their authority. However, in practice, there are still gaps, especially in the neutrality of village officials in handling conflicts in rural areas, which are often biased. Such impartiality certainly has an impact on the sense of trust in local officials and the social cohesion of the village community. This study analyzes the lack of neutrality of village officials in resolving conflicts in Suka Negeri Village, Lebong Regency. The aim is to describe how this lack of neutrality is not only an administrative issue but also a manifestation of power relations and social legitimacy that shape how law and justice are enforced. This study uses a qualitative case study approach. Research data was collected through semi-structured interviews and observations to gain an understanding of the conflicts that occurred and the resolution of cases by village officials. The theoretical framework uses Ralf Dahrendorf's conflict analysis to review the dynamics of pseudo-groups, interest groups, and conflict groups in the village social structure. This study fills a gap in research that tends to focus only on administrative governance in villages, without examining socio-cultural biases in conflict resolution. The findings show that village officials have not played a fair role in conflict resolution due to partiality and patronage that favor those with kinship ties to them, thereby fostering resistance and a crisis of trust. Adanya Undang-Undang Nomor 6 Tahun 2014 tentang Desa memberikan landasan hukum bagi perangkat desa dalam menjalankan kewenangannya. Namun dalam praktik masih terdapat kesenjangan, terutama pada netralitas perangkat desa dalam menangani konflik di pedesaan yang sering kali bias. Ketidaknetralan semacam itu tentunya berdampak pada rasa kepercayaan terhadap pejabat lokal dan kohesi sosial masyarakat desa. Penelitian ini menganalisis ketidaknetralan perangkat desa dalam penyelesaian konflik di Desa Suka Negeri, Kabupaten Lebong. Guna mendeskripsikan bahwa ketidaknetralan tersebut bukan hanya persoalan administratif, tetapi merupakan manifestasi relasi kuasa dan legitimasi sosial yang memengaruhi cara hukum dan keaadilan ditegakkan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, data penelitian dikumpulkan melalui wawancara semi struktur dan observasi untuk memperoleh pemahaman mengenai konflik yang terjadi dan penyelesaian kasus oleh perangkat desa. Kerangka teoritis menggunakan analisis konflik Ralf Dahrendorf untuk mengulas dinamika kelompok semu, kelompok kepentingan dan kelompok konflik dalam struktur sosial desa. Studi ini mengisi celah penelitian yang cenderung menyoroti tata kelola administratif desa saja tanpa menelaah bias sosial-budaya dalam resolusi konflik. Temuan menunjukkan bahwa perangkat desa belum menjalankan peran secara adil dalam penyelesaian konflik karena keberpihakan dan patronase yang memberi keuntungan bagi pihak yang memiliki hubungan kekerabatan ke pejabat desa sehingga memunculkan resistensi dan krisis kepercayaan.